Milieu Dalam Pendidikan Islam - Najahah, Najahah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2015)
Abstract: Environment is one the urgent thing in education wolrd because environment has funcion as a place where education process is taking place. He same as with social environment, it has important role for human being. As we know human being is social creature that created from a blood cloth or something that adherence on the uterus wall, but it is also can be understood that he uterus wall created always based on oher pary or it canât live by it self. So it can be understood that human being wih all characterization and their growth is the result of two achievment factors. Namely Heritage factor and environment factor. There factors influence human being in their interaction since they become embryo till to the end of their life.